Socioeconomic trajectory from birth to adolescence and lung function: prospective birth cohort study - Martínez-Mesa Jeovany; Wehrmeister Fernando C; Noal Ricardo B; Perez-Padilla Rogélio; Dumith Samuel C; Menezes Ana MB; Araújo Cora LP; Hallal Pedro C (BMC, 2011)
Abstract Background Socioeconomic status (SES) has been shown to be an important contributor to lung function. The aim of this study was to evaluate the association between lung function in adolescence and (a) SES at birth; (b) SES in adolescence; (c) SES trajectory from birth to adolescence ('never poor', 'non poor-poor', 'poor-non poor' and 'always poor'). Additionally, we investigate the role of adolescent and parental variables at mediating these associations. Methods Prospective birth cohort study in Pelotas, Brazil, including 4,005 adolescents (mean age: 14.7 years) followed up from birth. Lung function was measured by spirometry. Outcome variables were forced expiratory volume in one second in liters (FEV1) and forced vital capacity also in liters (FVC). Results Mean FEV1 was 3.46 L (95%CI 3.43-3.49) among boys and 2.93 L (95%CI 2.91-2.95) among girls. Mean FVC was 4.00 L (95%CI 3.97; 4.04) among boys and 3.30 L (95%CI 3.27; 3.32) among girls. SES at birth, in adolescence and its trajectory from birth to adolescence were inversely associated with lung function in both adolescent boys and girls. After adjustment for mediating variables, coefficients were largely reduced, particularly among boys, and the main predictor of change in coefficients was the inclusion of height in the models. Conclusion Low income adolescents from Brazil present impaired lung function as compared to the better off, and this is largely explained by height.